The Effectiveness of Quizizz Platform as a Media for the Evaluation of Akidah Akhlak Learning in Kudus Regency - Nailna Amanina; Ashif Az Zafi (Abjadia, 2021)
This study aims to determine the application of the Quizizz platform as a medium for evaluating Akidah Akhlak learning in Kudus Regency and to determine the effectiveness of the application of the Quizizz platform as an evaluation medium for Akidah Akhlak learning in Kudus Regency. This research uses quantitative descriptive analysis research. Then, this study gives results, namely in the evaluation of Akidah Akhlak learning in Kudus Regency during online learning using the Quizizz media platform and in this application it has a high effectiveness when implemented, with a percentage value of 56.17%. The implication of this research on learning is that the online evaluation process is more effective when using the Quizizz platform, especially in daily assessments.